A reconstruction of Middle Preclassic Maya subsistence economy at Cahal Pech, Belize - Powis, Terry G.
The recovery of animal and plant remains from the site of Cahal Pech provides data on early diet and subsistence practices in the Belize Valley region of the Maya lowlands. Analysis of the material remains suggests that the Middle Preclassic Maya were practising a mixed subsistence economy relying on agricultural foodstuffs, local terrestrial game species, freshwater fish and shellfish and marine reef fishes. Isotopic analysis of human bone is used to aid in the reconstruction of actual food consumption.